The Impact of Stress and Physical Activity on Premenstrual Syndrome Among Junior High School Female Students - Najamuddin, Nur Isriani; Nasir, Ramdani; Wahab, Masyitah; Nurfadhila, Nurfadhila (Yayasan Inspirasi El Burhani, 2024)
Background: Premenstrual syndrome (PMS) is a collection of physical, emotional, and behavioral symptoms that occur during the luteal phase of the menstrual cycle and often disrupt daily activities. Stress and physical activity are among the factors that may influence the occurrence and severity of PMS. Objective: This study aimed to determine the relationship between stress levels and physical activity with premenstrual syndrome among adolescent girls aged 12–15 years at SMP Negeri 4 Polewali. Methods: This research employed a quantitative analytic design with a cross-sectional approach. The population included all female students aged 12–15 years at SMP Negeri 4 Polewali. A total of [insert sample size] respondents were selected using proportional stratified random sampling. Data on stress levels were measured using the Perceived Stress Scale (PSS), physical activity levels were assessed using the International Physical Activity Questionnaire (IPAQ), and PMS was evaluated using the Premenstrual Syndrome Questionnaire (PMSQ). Data were analyzed using the Chi-square test to determine the relationship between variables. Results: The results showed a significant relationship between stress levels and PMS incidence (p < 0.05), where students with high stress levels were more likely to experience PMS. Physical activity also showed a significant relationship with PMS (p < 0.05), with low physical activity being associated with higher PMS incidence. Conclusion: There is a significant association between stress levels and physical activity with the occurrence of PMS among adolescent girls at SMP Negeri 4 Polewali. These findings suggest the importance of stress management and regular physical activity as preventive strategies for PMS in adolescents.